2020
DOI: 10.1186/s12957-020-02026-z
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic biomarkers related to breast cancer recurrence identified based on Logit model analysis

Abstract: Background This study intended to determine important genes related to the prognosis and recurrence of breast cancer. Methods Gene expression data of breast cancer patients were downloaded from TCGA database. Breast cancer samples with recurrence and death were defined as poor disease-free survival (DFS) group, while samples without recurrence and survival beyond 5 years were defined as better DFS group. Another gene expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, combination immunotherapy studies have shown better response compared to monotherapies using PD-1/PD-L1 inhibitors in cancer treatment [ 36 ]. Therefore, novel biomarkers associated with response to chemotherapy and prognosis should also be investigated to enhance the chemotherapy response and improve the outcome in TNBC [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, combination immunotherapy studies have shown better response compared to monotherapies using PD-1/PD-L1 inhibitors in cancer treatment [ 36 ]. Therefore, novel biomarkers associated with response to chemotherapy and prognosis should also be investigated to enhance the chemotherapy response and improve the outcome in TNBC [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel biomarkers associated with response to chemotherapy and prognosis should also be investigated to enhance the chemotherapy response and improve the outcome in TNBC [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, MRPL13 could indicate the poor prognosis of breast cancer. 11 However, the role of MRPL13 in NSCLC has not been described yet.…”
Section: Introductionmentioning
confidence: 99%
“…Tumorigenesis is often associated with alterations in the stromal environment and immune status, mainly manifested as changes in the tumor microenvironment (TME) [ 14 , 15 ]. TME plays a key role in several steps of tumor development, including local drug resistance, immune escape, recurrence, and distant metastasis [ 16 , 17 ]. Tumor cell exposure to TME also contributes to shaping the tissue-specificity of driver genes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%